الأساليب التربوية المستخدمة في مجال الثقافة الجنسية مع تلاميذ السنة الرابعة متوسط من وجهة نظر الأمهات - حمادو، أسماء (جامعة الوادي university of Eloued, 2019)
ملخص الدراسة: هدفت الدراسةالحالية للكشف عن الأساليب التربوية المستخدمة في مجال الثقافة الجنسية لدى تلاميذ السنة الرابعة متوسط من وجهة نظر الأمهات، حيث تم صياغة سؤالين للمشكلة على النحو التالي: مامستوى استخدام الأساليب التربوية في مجال الثقافة الجنسية من وجهة نظر الأمهات مع بناتهن اللواتي يدرسن في السنة الرابعة متوسط؟ هل يختلف استخدام الأساليب التربوية في مجال الثقافة الجنسية من وجهة نظر الأمهات مع بناتهن اللواتي يدرسن في السنة الرابعة متوسط وفقا لمتغير المستوى التعليمي؟ وقد ضمت عينة الدراسة 70 أماً تم توزيع على بناتهن الإستبيان الأساليب التربوية المعد من طرف الباحثة الذي يحتوي على خمسة أبعاد ، وقد تم إتباع المنهج الوصفي ( الإستكشافي ، الفارقي ) حيث إستخدمت الباحثة كل من النسبة المئوية وتحليل التباين الأحادي وتم التوصل إلى : أن مستوى استخدام الأمهات للأساليب التربوية في مجال الثقافة الجنسية مع بناتهن متوسط وقُدر بـ (64.28%) لاتوجد فروق بين الأمهات في استخدام الأساليب التربوية في مجال الثقافة الجنسية مع بناتهن فقاً لمستواهن التعليمي ، حيث قُدرت (0.03) Abstract: The study aimed at detecting the use of educational methods in the field of sexual culture from the point of view of mothers concerning the fourth year pupils at middle school. Two questions were formulated for the problem as follows: What is the level of use of educational methods in the field of sexual culture from the perspective of mothers towards their daughters who study in the fourth year of middle school? Does the use of educational methods in the field of sexual culture differ from the point of view of mothers with their daughters who study in the fourth year of middle school according to the educational level variable? The study included 70 mothers of whom the girls where given of the questionnaire “The educational methods”. The questionnaire prepared by the researcher has five dimensions. The descriptive approach (the explorative approach, the differential approach) was adopted. The researcher, then, used both the percentage and the analysis of the monographic diagram in addition to the application of the statistical tools. We concluded the following: The level of which mothers used the educational methods in the field of sexual culture with their daughters studying at middle school (fourth year) was average and estimated by (64.28%) There are no differences between the mothers concerning the use of educational methods in the field of sexual culture with their daughters according to their educational level. The values were estimated by (0.003)
دراسة إستكشافية لأمهات التلميذات بمتوسطتي جعفري يوسف 1 و 2 بجامعة
مذكرة ماستر في علوم التربية تخصص إرشاد وتوجيه
Keywords: الثقافة الجنسية، الأساليب التربوية; Éducation sexuelle, méthodes éducatives; Sexual education, educational methods